PREGAÇÃO NA TERRA DO SAMBA E DO FUTEBOL UMA ANÁLISE SÓCIO-RELIGIOSA DA PRÉDICA PROTESTANTE DE MISSÃO E A IDENTIDADE BRASILEIRA - Arakaki, Ricardo Augusto (2012)
This research paper has as its main purpose the identification of the socio-religious consequences that result from the encounter of typical protestant preaching and the principle reference marks of Brazilian identity. As such, in the first part, by means of a bibliographic review and a study of sermons by some of the first American missionaries and national preachers, it analyzes the religious movements that formed the theological matrix of the protestant mission and are responsible for the characterization of its preaching. Second, by means of field research and analysis of contemporary sermons, the research discerns variations in the protestant theological matrix of mission, understood in terms of its current preaching. Third, upon defining the primary aspects of national identity, it will confront the principle characteristics of the Brazilian protestant mission of preaching, and thus identify some socio-religious consequences deriving from these agreements and disagreements that result from the two phenomena. Finally, based on the results of the research and what has been written about the topic, some ways will be suggested for a homiletic that takes into account Brazilian identity as a basic element for reflection and practice and thus allowing for the elaboration of sermons that are not only done by Brazilians but for Brazilians.